Tailoring the composition of the AA2017 to reduce its hot cracking susceptibility during LPBF - Rojas Arias, Nicolas (2024)
Laser Powder Bed Fusion (LPBF) holds significant importance and research interest because of its capability to fabricate metallic components with intricate geometries that are challenging to replicate using traditional manufacturing methods. However, only a limited number of alloys are commercially viable for LPBF due to the processing conditions and characteristics of the alloys. This issue is particularly critical for alloys with wide solidification ranges such as wrought aluminum alloys, which may exhibit poor LPBF processability. For instance, previous experiments with the AA2017 alloy revealed its unsuitability for LPBF due to susceptibility to hot cracking. This study aimed to alter this alloy composition by incorporating additional elements that reduce the solidification range, facilitate grain refinement, and prevent crack formation during LPBF. The impact of different alloy element additions on the solidification range and phase formation was assessed via thermodynamic calculations. Compositions based on AA2017 were designed using the CALPHAD method and subsequently produced via gas atomization. The Design of Experiments methodology guided the selection of appropriate processing parameters to achieve crack-free parts with optimal structural integrity. Various characterization techniques were employed to examine the microstructural and mechanical properties. A new composition based on AA2017 was produced, enabling the construction of high-density, crack-free LPBF parts. X-ray diffraction analysis and microscopy techniques revealed that the improved processability of the new composition is attributed to its shorter solidification interval and a more fraction of liquid in the final stage of solidification with the presence of eutectic Al+Al3CeCu regions, which not only help to prevent crack formation but also enhanced the material's mechanical strength, as confirmed by the mechanical tests.